Study of skin neoplasms in a university hospital: integration of anatomopathological records and its interface with the literature - Hudson Dutra Rezende; Ana Paula Moura de Almeida; Eduardo Shimoda; Ana Carolina Xavier Milagre; Liana Moura de Almeida (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Background: Skin cancer is a highly prevalent condition with a multifactorial etiology resulting from genetic alterations, environmental and lifestyle factors. In Brazil, among all malignant tumors, skin cancers have the highest incidences. Objective: To retrospectively evaluate the incidence, prevalence and profile of basal cell carcinoma, squamous cell carcinoma and cutaneous melanoma in Campos dos Goytacazes and region. Methods: In total, 2,207 histopathological reports of a local reference hospital were analyzed between January 2013 and December 2015, of which 306 corresponded to the neoplasms studied. Results: Of the 306 reports evaluated, 232 basal cell carcinomas (75.9%), 55 squamous cell carcinomas (18%) and 19 cutaneous melanomas (6.5%) were identified. The face was the most involved anatomical site (58.8%) and women (51%) were the most affected gender. The temporal analysis revealed a decrease in the overall incidence of 3.4% from 2013 to 2014 and 5.4% from 2014 to 2015. There was a 10.1% increase in basal cell carcinomas and 38% in melanomas in this period; however, there was a decrease in the number of squamous cell carcinomas of 14.8% during the studied years. Study limitations: Some samples of cutaneous fragments had no identification of the anatomical site of origin. Conclusion: Research that generates statistical data on cutaneous tumors produces epidemiological tools useful in the identification of risk groups and allows the adoption of more targeted and efficient future prevention measures.